Chemical characterization and storage stability of extra virgin olive oil extracted from Derik Halhalı cultivar - Shendi, Esmaeil Ghanbari (Array, 2019)
Turkish olive cultivar known as “Halhalı” that is locally grown in Mardin (Derik) province, situated in the southeast Anatolia, was used for virgin olive oil (VOO) production. Halhalı olive was processed in the “Mobile Olive Oil Processing Unit” (TEM Oliomio 500-2GV, Italy) designed as the first mobile olive mill in Turkey. Some chemical and physical properties (colour, UV absorbance values, free fatty acid content, peroxide value, phenolic and tocopherol profiles) were determined and monitored during one year of storing in the dark at room temperature once in every three months. Results showed that up to the eighth month of storage, free fatty acid content, peroxide and UV-absorption values (K232 and K232 values) did not exceed the limits reported by International Olive Council (IOC) and olive oils were categorized as Extra Virgin Olive Oil (EVOO). Colour changed from green to yellow and UV absorbance values altered during storage. Total phenol and vitamin E (α- tocopherol) contents decreased by 18% and 16.38%, respectively. Luteolin and apigenin were the most abundant phenolics and their contents decreased up to 22% and 28% during storing, respectively.